2017
DOI: 10.1021/acs.biomac.7b00549
|View full text |Cite
|
Sign up to set email alerts
|

Sericin Promotes Fibroin Silk I Stabilization Across a Phase-Separation

Abstract: Natural silk spinning offers several advantages over the synthetic fiber spinning, although the underlying mechanisms of this process are yet to be fully elucidated. Silkworm silks, specifically B. mori, comprise two main proteins: fibroin, which forms the fiber, and sericin, a coextruded coating that acts as a matrix in the resulting nonwoven composite cocoon. To date, most studies have focused on fibroin's self-assembly and gelation, with the influence of sericin during spinning receiving little to no attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…This rise is most likely due to the dehydration of the proteins present, and the return to the baseline is due to either the structural reconfiguration of the proteins (e.g., gelation which agrees well with recent rheological studies) or could imply that proteins present are able to become partially rehydrated over the timescale of the experiment (discussed in more detail in Section S3, Supporting Information). This rehydration phenomena may be attributed to sericin itself, which is known to resolubilize more readily than fibroin (perfectly exemplified by degumming) or perhaps acting as a renaturing/protective agent for fibroin which is consistent with other recent observations, or finally, that certain portions of the fibroin protein are more hydrophilic than others (Section S3, Supporting Information).…”
Section: Resultssupporting
confidence: 73%
“…This rise is most likely due to the dehydration of the proteins present, and the return to the baseline is due to either the structural reconfiguration of the proteins (e.g., gelation which agrees well with recent rheological studies) or could imply that proteins present are able to become partially rehydrated over the timescale of the experiment (discussed in more detail in Section S3, Supporting Information). This rehydration phenomena may be attributed to sericin itself, which is known to resolubilize more readily than fibroin (perfectly exemplified by degumming) or perhaps acting as a renaturing/protective agent for fibroin which is consistent with other recent observations, or finally, that certain portions of the fibroin protein are more hydrophilic than others (Section S3, Supporting Information).…”
Section: Resultssupporting
confidence: 73%
“…Furthermore, we observe that sericin flows in a quasi-Newtonian manner throughout the fibroin shearing range (i.e. until UC,Fib), at which point its viscosity drops, which may be the result of selection for the need to maintain the consistent sericin-fibroin interface required for stable long-term fibroin storage [126], but later thin in order to ease the transport of an increasingly solid fibroin core through our recently proposed "solidity gradient" model [91]. These arguments are further supported by recent work into drying rates of newly spun fibres which found that the external (sericin) layers remain wet for several seconds [116], and that when spun under high humidity, flow can continue between cocoon layers [33], suggesting sericin does not solidify within the animal.…”
Section: Resultsmentioning
confidence: 84%
“…The Bombyx mori protein fiber is a composite material comprising a semi‐crystalline silk core (i.e., silk fibroin), which is mainly responsible for the load‐bearing capacity, and an outer layer of sericin, which functions as a gumming agent . However, emerging evidence suggests that sericin also inhibits the premature conversion of soluble silk (silk I) into β‐sheet‐rich silk …”
Section: Silk: Hierarchical and Crystal Structuresmentioning
confidence: 99%